PENGARUH PERBEDAAN DOSIS LIMBAH CAIR BIOETANOL (Vinasse) TERFERMENTASI TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Alfen Hasiholan; Armain Armain; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Bioethanol’s liquid waste (vinasse) is one of organic matter that pottentialy as organic fertilizer. The objective of this research was to observe the effect of vinasse and get the best dose on seedling growth of the cocoa plant. This research used completely randomized design non factorial consists of 5 treatments, they are without bioethanol’s liquid waste, 300 ml/polybag, 600 ml/polybag, 900 ml/polybag, 1200 ml/polybag. Each unit of treatment was repeated 4 times to obtain 20 units of experiment and the experimental unit comprises 4 plants, which is two of the plants used as plant samples. Parameters observed were plant height, number of leaves, steam diameter, leaf area, root volume, the ratio of crown roots and the dry weight. The results showed that significantly affect the bioethanol’s liquid waste increase in all parameters and the best treatment can be obtained by providing a dose of bioethanol’s liquid waste 600 ml/polybag. Keywords: Bioethanol’s Liquid Waste, Cocoa seedlings